10 - Race and Opportunity in the Transition from School to Higher Education in South Africa - Michael Cosser (Journal of Higher Education in Africa, 2009)
While South Africa is well into its second decade of democracy, higher education opportunities in the country remain different for different race groups. Black African learners are not represented in the first-year higher education enrolment profile (the intake of learners who proceed to higher education directly from school) in relation either to their representation in the general population or to their aspirations for entry into higher education. This much emerges from a triangulation of the findings of two surveys of Grade 12 learner aspirations for higher education study, conducted in 2001 and 2005, with analyses of the Higher Education Management Information System (HEMIS) enrolment profiles of 2002 and 2006. That the 2001– 02 aspiration-enrolment disjunction is replicated in the 2005–06 study, moreover, confirms the slow pace of educational transformation in the new democratic order. The key conclusion drawn from the juxtaposition of these two studies is that discrimination, while not overt, remains entrenched in South African educational pathways by virtue of the differential opportunities available to learners of different races – opportunities that are a function largely of socio-economic status (SES) and of the differential horizons for action which SES opens up for learners.